2018
DOI: 10.1021/acs.energyfuels.8b00107
|View full text |Cite
|
Sign up to set email alerts
|

Slurrying Property and Mechanism of Coal–Coal Gasification Wastewater–Slurry

Abstract: The co-slurrying technology of coal and organic wastewater, which achieves the simultaneous disposal and utilization of wastewater, has attracted extensive attention in recent years. The emission of coal gasification wastewater causes serious environmental hazards, because of its large amount, high organic content, and high toxicity. In the present study, two types of wastewater, namely, gasifier wastewater (GW) and wastewater from a secondary sedimentation tank (SW), were used to prepare coal water slurry (CW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Phenols can be absorbed on the surface of the coal particles through benzene rings, and the adsorption results in the improvement of the particle surface polarity. The thickness of the hydration layer increases and the content of free water decreases . Therefore, the apparent viscosity increased because of the existence of phenols, and the SC 1000 value of CCWS became lower than that of CWS.…”
Section: Resultsmentioning
confidence: 99%
“…Phenols can be absorbed on the surface of the coal particles through benzene rings, and the adsorption results in the improvement of the particle surface polarity. The thickness of the hydration layer increases and the content of free water decreases . Therefore, the apparent viscosity increased because of the existence of phenols, and the SC 1000 value of CCWS became lower than that of CWS.…”
Section: Resultsmentioning
confidence: 99%
“…2. Some studies have pointed out that ammonia nitrogen can be adsorbed on the surface of coal particles, [28] so that a thicker and more stable hydration film is formed around the particles, which increases the difficulty of releasing water molecules from the hydration film, thereby reducing MSC of CWWS. [29] Therefore, ammonia nitrogen is also one of the indispensable input factors.…”
Section: Pearson Correlation Analysismentioning
confidence: 99%
“…Several research papers have been published on the slurryability and rheology of coal slurries prepared with different types of wastewater−coal slurries, such as hydrothermal treatment waste liquid, 9 coal waste liquid, 10 gasification furnace wastewater, and secondary sedimentation tank wastewater. 11 Previous experiments have shown that slurrying is promoted by some types of wastewater, such as hydrothermal treatment waste liquid and coal waste liquid, but not by others, such as gasification furnace wastewater and secondary sedimentation tank wastewater. These responses can be mainly attributed to the different internal components of wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…CWS must have good slurrying properties, specifically, high concentration (heat value) and low viscosity, to ensure the economic efficiency of CWS-based combustion and gasification. Several research papers have been published on the slurryability and rheology of coal slurries prepared with different types of wastewater–coal slurries, such as hydrothermal treatment waste liquid, coal waste liquid, gasification furnace wastewater, and secondary sedimentation tank wastewater . Previous experiments have shown that slurrying is promoted by some types of wastewater, such as hydrothermal treatment waste liquid and coal waste liquid, but not by others, such as gasification furnace wastewater and secondary sedimentation tank wastewater.…”
Section: Introductionmentioning
confidence: 99%